VIOLENCE, ECONOMIC FACTORS AND IDENTITY FORMATION. THE CONSTRUCTION OF SOCIAL COHESION AMONG WARRIOR GROUPS IN THE VISIGOTHIC KINGDOM OF TOLEDO. - RUCHESI, FERNANDO (Imago Temporis. Medium Aevum, 2024)
With the settlement of the barbarians within the Roman Empire, during the fourth and fifth centuries, one way in which their integration took place was in relation to the Late Roman Army. At this point, barbarians and Romans exchanged trails related to a military identity, which worked as well as an element of cohesion. This manifested in traditions and rituals which were echoed both in the Merovingian Kingdorns as well as in the Visigothic Kingdom of Toledo. The aim of tlliS work is to analyse the ways in which social cohesion was constructed in relation to the army and groups who participated in military activities in the Visigothic Kingdom of Toledo. In order to do this, narrative, chronistic, and legal sources are analysed. We suggest that these processes of cohesion were influenced mainly by three factors that shaped their development: violence, the economic element, and the use and exhibition of a military identity.